South African Renal Registry Annual Report 2022 - Davids, M Razeen; Marais, Nicola; Sebastian, Sajith; Jardine, Thabiet; Chothia, Mogamat-Yazied; Jacobs, Julian C (African Journal of Nephrology, 2024)
This is the eleventh consecutive annual report of the South African Renal Registry since it was re-established and launched with the publication of the December 2012 data on kidney replacement therapy (KRT) in South Africa. The December 2022 data reported here indicate a continued increase in the number of patients on treatment following the COVID-19-related decrease which was previously recorded. There were 822 patients who started KRT in 2022, an incidence of 13.3 per million population (pmp). Most of these patients (77%) were treated in private centres. In December 2022, the total number of patients on treatment with chronic dialysis or transplantation stood at 9 342, up from 8 866 in 2021, an overall prevalence of 151 pmp. The prevalence was 771 pmp in the private healthcare sector. In the public sector, the overall prevalence was 45 pmp, with the Western Cape being the province with the highest public sector prevalence (165 pmp) and Mpumalanga the province with the lowest (3 pmp).